MARKETING PROCESS FROM THE SERVICE-DOMINANT LOGIC PERSPECTIVE - Мазуров, Антон В’ячеславович (Journal of Strategic Economic Research, 2024)
The article critically examines the limitations of traditional marketing approaches, which remain predominantly product-centric. During the research, the following methods were used: comparison, abstraction, analysis and generalization. In traditional marketing, the Segmentation, Targeting, and Positioning (STP) model heavily relies on analyzing broad market data – such as competitor dynamics, market size, and consumer demographics – while often neglecting to focus on the fundamental needs and goals of customers. These gaps are addressed by proposing a revised marketing process based on Service-Dominant Logic (S-D logic). Unlike traditional models that assume value is embedded in goods, S-D logic emphasizes that value is co-created by market actors in service ecosystems. This research takes S-D logic further by integrating it with the Outcome-Driven Innovation (ODI) and the Jobs Theory (JTBD), to find an actionable approach to developing marketing strategies that center on customer outcomes. The purpose of the study is to explore how businesses can adapt their marketing processes to be more outcome-driven and customer-focused. Research findings reveal that according to S-D logic service is defined as the process of using one’s resources, skills, and competencies for the benefit of another party. It shifts the focus from goods and transactions to solutions that meet customer needs. The results further demonstrate that ODI and JTBD, rooted in cognitive science, quality management, and usability engineering, provide a robust and practical framework for uncovering and addressing the needs that drive customer behavior. By leveraging ODI and JTBD as practical extensions of S-D logic, companies can systematically identify the core jobs that customers are trying to complete and align their marketing strategies with these customer needs. The service-dominant marketing process is offered with a more optimized and efficient structure compared to traditional methods due to introduction of the Market Discovery and Opportunity Identification phase, which allows outcome-based segmentation and better understanding of customers’ context.